Parental decision-making in taking care of child health in Indonesia: Findings from a national survey - Prasetyo, Yoyok Bekti; Fahad, Mochammad; Dewi, Yulis Setiya; Huriah, Titih; Latif, Rusnani AB (Faculty of Medicine, Universitas Islam Indonesia, 2024)
Background: The decision-making process to search for child health services involves interaction among the mother, partner, and other family members. Parental decision-making is highly complex since it involves an emotional consideration between the benefit and the child's future. The common problem in deciding the service is the lack of capabilities, such as facility, knowledge, and skill.Objective: The purpose of this study is to analyze the influence of socio-demographic factors on parents' decision-making in obtaining health services for their children Methods: This study design was cross-sectional data from the Indonesia Demographic and Health Survey (IDHS) of 2017, which was applied in this study. The respondents involved were 8,838 women aged 15-49 who had given birth in the last five years. This study employed descriptive, chi-square, and regression statistics analysis. The results were provided as adjusted odds ratios (AORs) with 95 percent confidence intervals. The statistical analysis utilized SPSS version 21.0 software (SPSS Inc., Chicago, IL, USA).Results: Bivariate analysis revealed a significant relationship between decision-making and age, living place, educational background, and wealth index (p-values 0.030, <0.001, 0.002, and 0.006), but not with health insurance ownership (p=0.242). After multivariate analysis, only age-related decisions were associated with a significant risk. It explained that younger group (15-29) has a 0.325 times chance of making a joint decision than the 40 to 49-year-old group (AOR: 0.325; 95%CI: 0.144-0.733). Conclusion: Parental decision-making regarding childcare is related to several factors, namely age, living place, educational background, and socioeconomic status. Health education is a strategy to promote child health in Indonesia by facilitating proper decision-making.